Conflict and competition : agōn in western Greece : selected essays from the 2019 Symposium on the Heritage of Western Greece - Reid, Heather Lynne, 1963-; Serrati, John; Sorg, Tim (Heritage of western Greece., 2020)
"The agōn deemed characteristic of ancient Greek culture has roots in the eris (strife) illustrated in Homer and Hesiod and debated in the metaphysics of Heraclitus and Empedocles...This volume considers agōn from a variety of disciplinary perspectives, with a special emphasis on Western Greece - the ancient Hellenic cities of Sicily and Southern Italy."--Page 4 of cover.